VARIES SHUTTLE RUN EXERCISE METHODS INCREASE AGILITY OF STUDENTS OF SMK NEGERI 2 TONDANO KABUPATEN MINAHASA - Sarapung, M; Pangkahila, J. A.; Adiputra, N.; Adiatmika, IPG (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2012)
ABSTRACT Achievment of Indonesian athletes at international level are only resting on badminton, archery, and weight lifting. Meanwhile, other sports do not exhibit encouraging achievement. Agility is one of the important factor on sports including group and individual sports. This is an experimental research with randomized pretest posttest conrol group design. Sample are 75 students recruited from SMK Negeri 2 Tondano Kabupaten Minahasa. Sample was grouped into 5 groups, each group composed of 15 students. The five groups observed were group 1 with treatment of 4 x 30 m shuttle run, group 2 treated with 8 x 15 m shuttle run, group 3 with 12 x 10 m shuttle run, group 4 within 16 x 7.5 m shuttle run, and the last is control group. Exercise was carried out for 6 weeks with a frequent of 3 time per week. Agility pre and posttest data were analysed using anova oneway followed by LSD Post Hoct Test at 5% significant level. This study obtained that there were a significant different among the five groups observed. Shuttle run exercise method with dose of 16x7.5 m increase the highest agility.
Keywords: achievement, agility, shuttle run, exercise